2014
DOI: 10.1080/01904167.2013.859696
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Petiole Sap Test for N Nutritional Status Assessing in Processing Tomato

Abstract: 2 A field experiment was carried out in Central Italy to assess the reliability of petiole sap for determining nitrogen (N) status on processing tomato. The crop was fertilized with different N rates and fertigation-irrigation frequencies. Reduced-N and nitrate-N concentrations were determined by lab analyses at 30, 42, 57, 71, and 84 days after transplanting. At each sampling date, the assessment of N nutritional status as resulted by sap test was compared with the actual plant N status as determined by nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…equipment are available for measuring the concentrations of ions in plant sap, such as colorimeters and specific ion electrodes (Hochmuth et al, 2004), that yield values with strong correlations (r 2 =0.96, p<0.0001) with those obtained from conventional laboratory analyses (Tully & Weil, 2014). This equipment has been used successfully in various crops, such as tomato (Hochmuth et al, 2004;Farneselli et al, 2014) and leafy vegetables such as lettuce, spinach, and Asian vegetables (Ott-Borrelli et al, 2009;Parks et al, 2012). However, it is difficult to interpret the results of sap analysis of crops, in particular, it is difficult to determine whether a nutrient is present in excess or is deficient and thus negatively affecting yield.…”
Section: Researchmentioning
confidence: 99%
“…equipment are available for measuring the concentrations of ions in plant sap, such as colorimeters and specific ion electrodes (Hochmuth et al, 2004), that yield values with strong correlations (r 2 =0.96, p<0.0001) with those obtained from conventional laboratory analyses (Tully & Weil, 2014). This equipment has been used successfully in various crops, such as tomato (Hochmuth et al, 2004;Farneselli et al, 2014) and leafy vegetables such as lettuce, spinach, and Asian vegetables (Ott-Borrelli et al, 2009;Parks et al, 2012). However, it is difficult to interpret the results of sap analysis of crops, in particular, it is difficult to determine whether a nutrient is present in excess or is deficient and thus negatively affecting yield.…”
Section: Researchmentioning
confidence: 99%
“…Xylem and phloem sap plus apoplastic solution are used to determine the nutrient concentration in a crop [4], but in order to establish a crop a nutritional diagnostic is required for comparison with the sufficiency ranges of this crop [5]. The sufficiency ranges are commonly used to interpret plant nutrient composition as well as nutrient deficiency, sufficiency, luxury consumption, or excess [6].…”
Section: Introductionmentioning
confidence: 99%
“…A significant correlation between NO 3 − and K concentration in petiole sap and N or K content in plant tissues has been observed for many vegetable crops [98,101,102]. However, experiments have highlighted the limits of this technique, and have shown that optimal values of nutrient concentration in the leaf petiole sap change as a function of (i) crop stage (values of sufficiency decline with crop age); (ii) cultivation system; (iii) species and cultivar and (iv) plant nutrient and water status [98].…”
Section: Plant Monitoringmentioning
confidence: 99%
“…Knowledge of the guide-values is thus critical to successfully apply the method, and this remains the main limitation for its practical application. However, reference values for N and also K are available for different types of vegetables grown in Florida [103] (Table 4), for melon and tomato in Almeria (Spain) [102], for potatoes in central and northern Europe [98], and for industrial tomato production in central Italy [101].…”
Section: Plant Monitoringmentioning
confidence: 99%